Enhancing English Listening Skill Using The Whisper Race Game - Trisnawati Trisnawati; Sukmawati Yasim; Nurul Imansari (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2023)
This study examines the effect of using the Whisper Race Game on listening skills learning in Majene 5 Middle School students as English as foreign language learners. Based on the preliminary study in this school, the researcher found that listening was the most challenging aspect of English for students. The study was also intended to figure out the student's perceptions. The quantitative method was implemented with a quasi-experimental design. The data were analyzed by using the Likert scale. The samples of this study were two groups consisting of 14 students for the control group and 14 students for the experimental group number of students were selected randomly due to the limited number of students in this school. The researcher used a listening test (pretest and posttest) as an instrument. The study results show that the Whisper Race game method can significantly improve students' listening skills.